Grafting: A New Approach to Improve Oil Palm? - Labeyrie, A.; Brossier, R.; Collin, M.; Wurth, E.; Ilbert, P.; Hibberd, J.; Tripathi, A.; Tregear, J.; Jacob, F.; Morcillo, F. (Fedepalma, Cenipalma, 2025)
Until very recently, grafting was thought to be impossible to achieve with monocotyledons, due to their lack of a vascular cambium and the scattered distribution of vascular bundles within the stem, preventing the establishment of functional connections between the scion (above-ground, epibiote) and rootstock (below-ground, hypobiote) portions of the plant.
Keywords: Injertos; Productividad; Palma de aceite